Studi Molecular Docking Senyawa Isolat Voacanga foetida sebagai Inhibitor Tirosinkinase pada Sel Kanker Payudara (MCF-7) - Ikhsal Mukri Jumadila; Adriani Susanty; Enda Mora; Roscha Ulfa Frasesa (LPPM Universitas Abdurrab, 2026)
Breast cancer remains one of the leading causes of cancer-related mortality worldwide, necessitating the development of targeted therapies with improved efficacy and lower toxicity. This study aimed to evaluate the potential of alkaloid isolates from Voacanga foetida, namely voacangine and vobtusine, as tyrosine kinase inhibitors against MCF-7 breast cancer cells through an in silico approach. Molecular docking was performed using Molecular Operating Environment (MOE) 2024 against tyrosine kinase protein with PDB ID: 1T46, followed by ADME and drug-likeness prediction using SwissADME and ADMETlab. Doxorubicin was used as a positive control. The docking results demonstrated that voacangine and vobtusine exhibited competitive binding affinities of -7.80 and -7.70 kcal/mol, respectively, with RMSD values below 2 Å, indicating stable ligand–protein interactions. Both compounds formed hydrogen bond interactions with key active residues HIS790 and ARG791. ADME analysis revealed that voacangine possessed the best drug-likeness profile, while vobtusine showed favorable conformational stability and low probability as a P-glycoprotein substrate. In conclusion, voacangine and vobtusine exhibit promising potential as natural tyrosine kinase inhibitor candidates for targeted breast cancer therapy and warrant further in vitro and in vivo investigations.